?BENEFICIATION OF HAZARA BARITE AS RAW MATERIAL FOR DIFFERENT BARITE UTILIZING INDUSTRIES (Biological Sciences - PJSIR, 2000)
Three barite deposits of economic importance occur near Haripur, Havelian and Kohala in HazaraDivision. Beneficiation studies of eighteen representative samples from these deposits were undertaken by chemical method. The objective of this study was to upgrade the quality of barite to acceptable limit for utilization in various industries. Simple treatment for 15 min with commercial hydrochloric acid has been suggested to obtain the required specification for 80% barite utilizing industries.